Organizational Justice In Higher Educations - Harvey Hiariey; Saleh Tutupoho (Universitas Medan Area, 2020)
Organizational justice is a central theme adopted by many studies in the last 30 years, it is the perception of members/workers of organization about what is fair and unfair in the organization where they work with. In the last few decades, private higher educations are grown well. There are difference in the funding or operational contexts between public and private higher educations. This difference leads also to the difference in organizational justice system. Meanwhile, research examining the difference of organizational justice between these two types of higher educations is still few. This paper is then aimed to explain the difference of organizational justice among higher educations based on preliminary empirical studies and normative reviews on relevant documents. This paper is also a prescription for empirical studies in understanding organizational justice at two types higher educations.